G170(P) Improving antenatal detection rates of significant congenital cardiac lesions in a district general hospital. (27th April 2015) - Aughey, H; Guilder, L; Kumar, Y
Abstract : Introduction: Congenital heart disease (CHD) affects around 1% of pregnancies in the UK each year. Around half of these are major cardiac lesions requiring surgery or intervention within the 1 st year of life. Studies show that if CHD is detected before birth, there are significant benefits for babies, their families and for medical services around the time of birth and in the first year of life. Prenatal diagnosis and appropriate treatment may prevent the devastating consequences of early circulatory collapse, such as death and ischaemic brain damage. Background: An audit previously conducted in our district general hospital found that the antenatal detection rate of significant cardiac lesions in Jan 1998–Dec 1999 was 17.6%. Following this, new ultrasound machines were purchased and ultrasonographers received training to perform outlet views of the fetal heart as well as 4 chamber views. Aims: The aims of this audit were 1) to establish whether this intervention has led to improved antenatal detection of significant CHD and 2) to compare these detection rates with national figures. Methods: Antenatal detection rates of CHD were again audited for all babies who received an anomaly scan in Jan 2009–Dec 2010. Children with significant CHD were identified through their attendance at cardiac clinic. We then looked retrospectively at each child's anomaly scan (18+0 – 20+6 weeks gestation) and recorded whether or not a cardiac lesion had been detected antenatally. We also reviewed data from the South West Congenital Anomoly Register (SWCAR) and local electronic and paper records by which method we were able to include antenatally detected significant CHD in foetuses who did not survive. Results: Following the intervention antenatal detection of significant CHD rose to 72%. This compares with national detection rates of around 30% over the same period. Conclusion: Our findings confirm the necessity of cardiac outlet views along side 4-chamber views as part of antenatal anomaly scanning with good supervision and support from local and regional Fetal Medicine Specialists.